O Projeto Somar na gestão do governo Zema (2019-2022): educação pública x interesses privados - Rodrigues, Lara Cristina Evaristo (2023)
The present study is inserted in the Research Line State, Policies and Management in Education of the Postgraduate Program in Education of the Federal University of Uberlândia, having as object of investigation the Somar Project, as part of the programs and actions implemented in the area of education in the government of Romeu Zema (2019-2022). The study aims to analyze the proposal of the Somar Project, a policy that provides for the shared management of secondary education through partnerships with private social organizations in the state network in Minas Gerais, in the Romeu Zema government (2019-2022), and the relationship with the defense of privatization and advance of capital over public education. Regarding the methodological procedures, the qualitative approach was the position taken in this research. A bibliographical research was carried out, with the purpose of deepening the theoretical framework that will support the research and the subsequent analysis of the data collected. In the second moment, a documental research was carried out in order to search the official documents of the Romeu Zema government and the State Education Secretary of Minas Gerais for data about the Somar Project. In addition to the documentary research, to investigate the implementation process of the Somar Project we used an interview with a state representative and with teachers who worked in the three selected schools in Minas Gerais, who, for confidentiality purposes, will not be identified in this report. As a result, it is possible to verify that the Somar Project, a recent and ongoing policy, deserves to be monitored and problematized in order to denounce its tricks and traps that are part of a totality of counterreforms and offensives of the neoliberal logic that brings setbacks to the right to education and the management of public schools. The analyses made about the Somar Project show that this experience represents a strong strategy for the advance of the privatization process of Minas Gerais' education, as a form that capital uses to advance on public services and rights. Although the research does not present data and information about the implementation process on the floor of the selected schools after the transfer to the “OSC” (because the project is in the implementation phase), the information and the statements of the people directly involved point to the dismantling of rights, leading to setbacks for education workers, students, and for the state network as a whole.